Complementarity and Deconstruction: A Comparative Study of Gender Hermeneutics in the Thought of Zainab al-Ghazali and Fatima Mernissi - Yuhanida, Yuyun; Nur Arfiyah Febriani; Ahmad Thib Raya (Institut Agama Islam Negeri Kendari, 2026)
Gender discourse in contemporary Islam faces tension between efforts to maintain the authenticity of tradition and the need to respond to demands for gender justice. Patriarchal bias in classical interpretation has marginalized women’s perspectives, creating an urgent need to reinterpret Qur’anic verses related to gender relations. This study aims to comparatively analysed the thoughts of Zainab al-Ghazali and Fatima Mernissi in formulating the concept of gender in Islam. The comparative model used covers three main dimensions: the epistemology of interpretation, the gender hermeneutic approach, and the practical implications in the contemporary Muslim context. The method used is descriptive-comparative with content analysis of the primary works of both figures, namely Naẓarāt fī Kitāb Allāh and Women and Islam: An Historical and Theological Enquiry. The findings show that Zainab developed a reformist-traditionalist approach through the concept of gender complementarity that emphasizes moral equality within the framework of role differentiation, with a naqliyyah epistemology rooted in the text. In contrast, Mernissi uses a deconstructive approach based on historical-sociological analysis to critique patriarchal bias in the Islamic exegetical tradition, relying on a critical epistemology that places the socio-historical context as the key to interpretation. Both approaches have significant contributions but also face their respective epistemological and methodological limitations. This study recommends the integration of both approaches to build a gender-responsive Qur’anic hermeneutics, with practical implications for the development of family jurisprudence and gender equality policies, especially in the context of moderate Indonesian Islam.